Edukasi Sumberdaya alam yang Lestari Melalui Pengenalan Tumbuhan Obat Keluarga (TOGA) Pada Generasi Muda di Kecamatan Mandor, Kalimantan Barat: Indonesia - Mariani, Yeni; Yusro, Fathul; Yanti, Hikma (UII, 2024)
Nature provides many benefits for humans, including the existence of plants that have medicinal properties. Currently, many people cultivate medicinal plants around the house and make them into family medicinal plants (TOGA). Providing education to the younger generation regarding the use of plants as family traditional medicine (TOGA) is important to increase the awareness of the younger generation in preserving natural resources. This Community Service activity was carried out in two stages, namely (1) preparation and collection of educational material followed by (2) delivery to educational participants, the young generation in Mandor District, Landak Regency, West Kalimantan. Educational activities are carried out through brochures/leaflets, stand banner and PPTs which are delivered at PKM activities. The younger generation, namely high school students, are enthusiastic about taking part in activities. There has been an increase in the knowledge and understanding of the younger generation regarding types of family medicinal plants, their benefits, processing methods and utilization by an average of 24.67%.